IMPROVING STUDENTS’ READING COMPREHENSION BY USING LOOK AND SAY METHOD AT SMP TRI SAKTI 1 MEDAN IN THE ACADEMIC YEAR 2021/2022 - Lumban Batu, Mei Yusnita; Sembiring, Novalina; Pangaribuan, Jontra Jusat (Kairos English Language Teaching Journal, 2022)
This research was conducted in order to improve students’ Reading Comprehension on Descriptive Texts through Look and Say method and to know the students’ responses towards the learning reading comprehension through Look and Say method at SMP Tri Sakti 1 Medan. In conducting this research, the writer used Classroom Action Research (CAR). This research showed that teaching reading comprehension through Look and Say method at SMP Tri Sakti 1 Medan could improve their reading comprehension. The result of the test showed that the students’ mean score in pre-test is 76.75, in formative test the mean score is 80.90, and in post-test the mean score is 85.62. The writer concluded that Look and Say method could improve the seventh grade students’ reading comprehension on descriptive texts of SMP Tri Sakti 1 Medan. On the other hand, the students’ responses towards the method of the teaching sound good because above 90% of the students are interested, motivated and understand the lesson with the Look and Say method.